Analisis Hukum Perdata Islam mengenai Wasiat Terhadap Putusan Mahkamah Agung Nomor: 379 K/AG/2009 - Rahman, Lingga Abi; Ermia, Vivin (Berasan: Journal of Islamic Civil Law, 2023)
The purpose of this study is to answer the question of how the analysis of Islamic Civil law regarding wills in the Supreme Court Decision Number: 379 K/AG/2009. A will is made with the aim that the heirs cannot know whether the inheritance left by the testator will be inherited by his heirs or whether it will be inherited by another party who is not at all |heirs until the time comes to read the will. In particular, testamentary items must not exceed 1/3 of the assets of the testator, if this is the case then it could be considered not in accordance with the will rules. The results of this analysis found that the will does not have an absolute position to be carried out/executed. This can happen if the execution of the will is obstructed by the owner of the object of the will. Therefore, it can be said that a will made as a last will is not necessarily a last will, because it can be canceled or annulled by law. Cancellation is carried out if the disputing party submits the matter to the court, then the position of the will becomes not absolute to be implemented if the will is an nulled or an nulled by law incourt. The importance of a will in estate planning lies not only in the distribution of assets, but also in the arrangement of issues such as dependents and obligations. Thus, a will becomes a vital legal instrument in protecting a person’s interests and wishes after death.